2016
DOI: 10.1111/apt.13531
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus vs. anti‐tumour necrosis factor agents for moderately to severely active ulcerative colitis: a retrospective observational study

Abstract: SUMMARY BackgroundThere have been no comparative studies of tacrolimus vs. anti-tumour necrosis factor (anti-TNF) agents to determine which treatment is safer or more effective in refractory ulcerative colitis (UC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 21 publications
2
58
1
5
Order By: Relevance
“…Yamamoto et al [9] have reported that for 100 patients with moderate to severe UC, the clinical remission rate after 12 weeks was 28% and 40% in the anti-TNF agents and Tac groups, respectively. Serum albumin and CRP levels at baseline were not statistically different between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamamoto et al [9] have reported that for 100 patients with moderate to severe UC, the clinical remission rate after 12 weeks was 28% and 40% in the anti-TNF agents and Tac groups, respectively. Serum albumin and CRP levels at baseline were not statistically different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…No differences between the groups were found in clinical disease activity using the partial Mayo score. The median partial Mayo score at base line was 7 (IQR, 6-7) in the IFX group vs. 6 (IQR, [3][4][5][6][7][8][9] in the Tac group (P = 0.600). In the laboratory data, hemoglobin was not different between the groups; however, the WBC, serum albumin and CRP were different.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flow diagram which describes the reasons for citations exclusion. Finally, 22 studies (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)28,30,32,33) that fulfilled eligibility criteria were included. Only two studies were randomized controlled trials (24,25) (Ogata 2006 and Ogata 2012); these were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…During the last few years, there has been a significant development of scientific evidence showing the benefit of biological therapy -mainly anti-TNF α agents -in both scenarios (7) . Nevertheless, approximately 30% of patients with moderateto-severe disease, whether they are CD or UC patients, do not respond to anti-TNF α therapy (primary failure) (3) and a significant proportion of patients (13% to 25% per year of treatment) may develop resistance and hence loss of efficacy to this type of treatment (secondary failure) (27,33) . This is why alternative therapeutic strategies are needed for these patients so that clinical conditions are improved and potentially serious complications can be avoided.…”
Section: Introductionmentioning
confidence: 99%